Improving the quality of theoretical training of cadets with the help of information and communication technologies - V. V. Bulgakov (Открытое образование (Москва))
Purpose of research. The aim of the study is to assess the relevance and effectiveness of the multi-level modular automated system of training, control and analysis of theoretical knowledge, developed and implemented in the educational process of the Ivanovo Fire and Rescue Academy of the State Fire Service of the Ministry of Emergency Situations of Russia, implemented in the form of a computer program Fire Test. The urgency and necessity of developing a computer program due to the peculiarities of educational process in institutions of the system of the Ministry of Emergency Situations of Russia, associated with the separation of cadets from the training sessions to carry out preventive measures and emergence rescue operations in response to fires and emergencies, the need to replenish the educational material and increase the intensity of theoretical training. Freely available computer programs, designed for theoretical training and control, often have limitedfunctionality, and programs with more functionality do not allow organizing training in accordance with the security requirements for personal and service data, established in the Ministry of Emergency Situations of Russia.Materials and methods. To study the effectiveness of the computer program Fire Test in the educational process, the methods of scientific and pedagogical research were used, the main of which were observation and pedagogical experiment. Methods of synthesis and analysis of information processes, methods of statistical analysis were used to summarize the experimental data. For estimating the demand among cadets and Faculty of the Fire Test computer program diagnostic tools were used, available in the program, as well as the service “Yandex.Metrics".Results. To assess the effectiveness of the program Fire Test the research was carried out on the level of theoretical knowledge of cadets of experimental groups, studying within the context-integration model and undergoing theoretical training through a multi-level modular automated system for teaching, monitoring and analyzing theoretical knowledge and cadets of control groups, studying in the traditional form. On the basis of the obtained test data, it is concluded that the introduction of the Fire Test program into the educational process has a statistically significant impact on the process of theoretical training and contributes to improving the level of theoretical training of cadets. The results are confirmed by a statistical criterion based on the student’s distribution, with a possible relative error of not more than 5%.The demand of the Fire Test program among the Faculty is confirmed by the dynamics of its application for the organization of testing and control of theoretical training. In the 2018-2019 academic year, the number of tests, created for checking the theoretical knowledge of cadets in the Fire Test program increased 3.3 times compared to the 2017-2018 academic year. Cadets for theoretical training most often use mobile devices that allow regardless of time and location to have access to theoretical material for its study and self-control.Conclusion. The results of the application of Fire Test programs in the educational process have shown its demand among students and Faculty, which is confirmed by the diagnostic monitoring tools of the “Yandex.Metrics " and service itself. The Fire Test program is an effective tool for theoretical training and control and contributes to improving the level of theoretical knowledge of cadets, which is confirmed by experimental studies conducted in the period from 2017-2018 to 2018-2019 academic year.